Toxic epidermal necrolysis probably due to cosmetic cream: a case report - Kokcam, I. (Dermatovenerological Soc Slovenia, 2009)
Toxic epidermal necrolysis (TEN) is a severe and life-threatening cutaneous reaction usually caused by systemic drug administration. Preparations applied to the skin and mucous membranes topically very rarely induce TEN. We present a case of TEN in a 35-year-old woman probably due to facial application of an over-the-counter (OTC) cosmetic cream.
Keywords: toxic epidermal necrolysis; over-the-counter cosmetic preparation; adverse effect